2010
DOI: 10.1007/s10964-010-9591-9
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Relations and Offending During Young Adulthood

Abstract: There is a long tradition of studying parent-child relationships and adolescent delinquency. However, the association between parent-child relationships and criminal offending during young adulthood is less well understood. Although the developmental tasks of young adulthood tend to focus on intimate relationships, employment, and family formation, the parent-child bond persists over the life course and likely continues to inform and shape behavior beyond adolescence. Using data from the Toledo Adolescent Rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 54 publications
5
51
0
Order By: Relevance
“…Day and Padilla-Walker (2009) reported that maternal connectedness was positively associated with prosocial behavior in adolescents after controlling for self-regulation. Furthermore, Johnson et al (2011) found parental support to be associated with lower levels of delinquency, describing this effect as persistent even in models considering peer influence. Thus, sensitive and supportive parenting seems to function as a "buffer" that reduces the risk of a child or adolescent from taking a developmental path that involves criminal and antisocial behavior.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Day and Padilla-Walker (2009) reported that maternal connectedness was positively associated with prosocial behavior in adolescents after controlling for self-regulation. Furthermore, Johnson et al (2011) found parental support to be associated with lower levels of delinquency, describing this effect as persistent even in models considering peer influence. Thus, sensitive and supportive parenting seems to function as a "buffer" that reduces the risk of a child or adolescent from taking a developmental path that involves criminal and antisocial behavior.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies were not based on a general population sample, instead focusing on specific groups, such as criminal offenders (Schimmenti 2014;Lahlah 2013;Kimonis 2013;Simons 2008;Wileman 2008;Palmer 2007;Kiriakidis 2006). Eleven studies evaluated both male and female participants (Schimmenti 2014;Nunes 2013;van der Voort 2013;Delhaye 2012;Sousa 2011;Ingoglia 2011;Johnson 2011;Hiramura 2010;Day 2009;Tyler 2006;Heaven 2004), whereas six studies exclusively evaluated male participants (Lahlah 2013;Kimonis 2013;Simons 2008;Wileman 2008;Palmer 2007;Kiriakidis 2006). Most studies were quantitative; however, some studies employed a cross-sectional (Nunes 2013;Lahlah 2013;Kimonis 2013;Delhaye 2012;Ingoglia 2011;Hiramura 2010;Day 2009;Simons 2008;Palmer 2007;Kiriakidis 2006;Heaven 2004) or longitudinal design (van der Voort 2013;Sousa 2011;Johnson 2011;Tyler 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations